A combined fugacity and multi-axial ductility damage approach in predicting high temperature hydrogen attack in a reactor inlet nozzle. (November 2020) - Chavoshi, Saeed Z.; Hill, Lance T.; Bagnoli, Kenneth E.; Holloman, Ryan.L.; Nikbin, Kamran M.
Highlights: Combined numerical model to predict hydrogen attack at elevated temperatures. A progressive failure based approach at the meso-macro level to predict actual damage in an industrial nozzle. Detailed sensitivity analysis carried out based on available materials data. Abstract: High temperature hydrogen attack (HTHA) and creep damage and cracking are time-dependent phenomena which can occur at relatively low temperatures (300–500 °C) in low alloy steel components used in petroleum refinery and petrochemical plant. The present study combines a novel multiaxial ductility creep model with a sub-grain level fugacity partial pressure strain-based failure criterion due to a build-up of methane gas to predict progressive damage accumulation and HTTA degradation in an aging nozzle component. Finite element (FE) simulations using appropriate subroutines for the coupled approach allow progressive failure predictions combining HTHA and creep deformation in a C-0.5Mo steel inlet nozzle which had seen 80, 000 h operation. A sensitivity study has been carried out to quantify the effects of different operating temperatures, failure strains, hydrogen concentration and pressure and material hydrogen diffusivity on the levels of damage in the nozzle over its lifetime. The predictions accurately bound the measured damage observed in the nozzle component and highlight the sensitivity of the model with respect to the input variables.